Evaluation of Polymerization Efficacy in Composite Resins via FT-IR Spectroscopy and Vickers Microhardness Test - Tahereh-Sadat Jafarzadeh; Mohammad Erfan; Marjan Behroozibakhsh; Mostafa Fatemi; Reza Masaeli; Yashar Rezaei; Hossein Bagheri; Yasaman Erfan (Tabriz University of Medical Sciences, 2015)
Background and aims. Polymerization efficacy affects the properties and performance of composite resin restorations.The purpose of this study was to evaluate the effectiveness of polymerization of two micro-hybrid, two nano-hybrid and one nano-filled ormocer-based composite resins, cured by two different light-curing systems, using Fourier transformation infrared (FT-IR) spectroscopy and Vickers microhardness testing at two different depths (top surface, 2 mm). Materials and methods. For FT-IR spectrometry, five cylindrical specimens (5mm in diameter × 2 mm in length) were prepared from each composite resin using Teflon molds and polymerized for 20 seconds. Then, 70-μm wafers were sectioned at the top surface and at2mm from the top surface. The degree of conversion for each sample was calculated using FT-IR spectroscopy. For Vickers micro-hardness testing, three cylindrical specimens were prepared from each composite resin and polymerized for 20 seconds. The Vickers microhardness test (Shimadzu, Type M, Japan) was performed at the top and bottom (depth=2 mm) surfaces of each specimen. Three-way ANOVA with independent variables and Tukey tests were performed at 95% significance level. Results. No significant differences were detected in degree of conversion and microhardness between LED and QTH light-curing units except for the ormocer-based specimen, CeramX, which exhibited significantly higher DC by LED. All the composite resins showed a significantly higher degree of conversion at the surface. Microhardness was not significantly affected by depth, except for Herculite XRV Ultra and CeramX, which showed higher values at the surface. Conclusion. Composite resins containing nano-particles generally exhibited more variations in degree of conversion and microhardness.